Генеза и својства на почвите образувани врз варовници и доломити во Република Македонија - Маркоски, Миле (Факултет за земјоделски науки и храна, УКИМ, Скопје, 2013)
The soils formed upon lime stones and dolomites in different locations of the territory of the Republic of Macedonia have been examined. The filed researches have been performed in the course of 2010, 2011 and 2012 during which 52 basic pedological profiles were excavated, 34 of which are calcomelanosols, 13 calcocambisols and 5 profiles of red soils (terra rossa). The genesis of these soils, the evolution, classification, the mechanical composition, the aggregate composition, the bulk and the real density of the soil, the porosity, the retention and the retention curves, the mineralogical composition of the soils and the chemical properties have been described. These soils are characterized with a profile type O-A-R; A-R; A-(B)rz-R. The contents of the fine soil separates in the calcomelanosols vary depending on the sub type. The physical sand fraction (coarse+fine sand) in the Amo horizon amounts 44,81% at the organomineral calcomelanosols 40,13% at the organogenic and brownised calcomelanosols 36.52%. In the (B)rz horizon at the brownised calcomelanosols amounts 32,64%. The contents (clay + silt) or physical clay in the Amo horizon amounts 55,19% at the organomineral calcomelanosols 59,87% at the organogenic and the highest content is at the brownised calcomelanosols 63,48%. The average value of this fraction in the horizon (B)rz at the brownised calcomelanosols amounts 67,36%. In the calcocambisols the average content of the fraction physical sand in the Amo horizon amounts 33,43%, and in the cambic horizon (B)rz 22,50%. At the terra rossa the fraction physical clay is represented with a greater percentage related to the physical sand fraction. In the Amo horizon in the physical clay fraction the clay fraction is predominant, average 43,08% and 52,13% in the cambic horizon, i.e. 24,90% in Amo and 19,37% for the silt fraction. The soils formed on limestone and dolomites most often have grain structure, but it can vary depending on the development stadium of the soil type and subtype. Out of the three soil types, calcomelanosols have the lowest average value of bulk density. Due to the greater quantity of organic matter in the subtype organogenic calcomelanosols, the bulk density of the Amo horizon has the lowest value (0.82 g/cm3) compared to the remaining sub-types. There is the highest retention capacity, average 41.48% under pressure of 0.33 bar, in the humus-accumulative horizon Amo in the subtype organogenic calcomelanosols. The remaining subtypes have lower retention in this horizon. The average retention values (pressure of 0.33 bar) in the Amo horizon and the cambic horizon (B)rz regarding calcocambisols amounts to 33.49% i.e., 33.24%. The average retention in terra rossa, under pressure of 0.33 bar, amounts to 39.05% in the Amo horizon, and 40.25% in (B)rz. The mineralogical composition of the parent material influences the amount of exchangeable base cations in the soil adsorptive complex. In all studied profiles, most present is the kaolinite, then illite and vermiculite. The remaining minerals, such as smectite, chlorite, mixed-layer minerals, and boehmite, have different presence in the tested profiles, which influences many properties of soil. Calcomelanosols are characterized with the highest content of humus in relation to the other soils formed on limestone and dolomite. The subtype organogenic calcomelanosols has highest mean value (19.47%). The content of humus in the Amo horizon amounts to 8,50% on average, and in the cambic horizon (B)rz 5.18%. In terra rossa, the average content of humus in the Amo horizon amounts to 5.33%, and in the cambic horizon B(rz) it amounts to 2.13%. pH in H2O in the sub-type organogenic calcomelanosols is an average of 6,99, average value of (6,93) belong to the organomineral calcomelanosols. In the Amo horizon with the brownised calcomelanosols is 6,12 and in the cambic horizon (B)rz, mean 6,68. In calcocambisols there is debasefication and acidification, due to which the soil solution is acidified and in the Amo horizon and (B)rz the average value of pH in H2O is 6,63. In the terra rossa the mean pH in H2O in the humus- accumulative Amo horizon is 6,94 and in the cambic horizon (B)rz 6,72. The highest cation exchange capacity (T) appears in the humus-accumulative Amo horizon (57,83 cmol(+)kg-1) with the organominerals calcomelanosols. The average values of the cation exchange capacity in the calcocambisols in the humus- accumulative Amo horizon is (59,53 cmol(+)kg-1) and in the cambic horizon (B)rz 48,57 cmol(+)kg-1. In the case of the terra rossa, the cation exchange capacity in the humus-accumulative horizon (Amo) the average is 44,62 cmol(+)kg-1, and in the cambic horizon (B)rz 48,72 cmol(+)kg-1. The sum of exchangeable base cations with the highest value appears with the humus- accumulative Amo horizon (48,43 cmol(+)kg-1) with the organomineral calcomelanosols. With the calcocambisols in the humus-accumulative Amo horizon, it is 48,18 cmol(+)kg-1, and in the cambic horizon (B)rz, 36,54 cmol(+)kg-1. With the terra rossa the average value of (S) in the humus- accumulative Amo horizon is 28,01 cmol(+)kg-1, and in the cambic horizon (B)rz, 33,22 cmol(+)kg-1 soil. The exchangeable Ca2+ dominates in the adsorption complex, followed by Mg2+, K+ and Na+. Highest average value of exchangeable Ca2+ (38,15 cmol(+)kg-1), in the Amo humus-accumulative horizon, is found in the organogenic calcomelanosols, subtype, then (29,84 cmol(+)kg-1) in the organomineral calcomelanosols and (23,60 cmol(+)kg-1) in the brownised calcomelanosols. In the brownised calcomelanosols subtype, in the (B)rz cambic horizon, it is amounting to 28,16 cmol(+)kg-1. The average content of exchangeable Ca2+ in the calcocambisols, in the Amo humus-accumulation horizon, is amounting to 32,91 cmol(+)kg-1 or (57,07% of Т), while in the (B)rz cambic horizon it is amounting to (26,52 cmol(+)kg-1 soil) or (56,26% of Т). Regarding the terra rossa, the average content of exchangeable Ca2+ in the humus-accumulative horizon (Amo) is amounting to 24,85 cmol(+)kg-1 soil or (59,28% of T). The average content of (H++Al3+) in calcomelanosols, in the Amo humus-accumulative horizon, in the organogenic soil subtype, is amounting to 10,70 cmol(+)kg-1 or (19,40% of Т), for the organomineral soils it is amounting to 9,36 cmol(+)kg-1 or (18,17% of Т) and 12,92 cmol(+)kg-1 or (31,39% of Т), while for the brownised calcomelanosols and in the (B)rz cambic horizon of the same subtype, it is amounting to 13,81 cmol(+)kg-1 or (33,89% of Т).The average values of the exchangeable (H+ +Al3+) in the humus-accumulative horizon are amounting to 11,30 cmol(+)kg-1 soil or (22,86% of Т), and 11,72 cmol(+)kg-1 soil or (25,27% of Т) in the (B)rz cambic horizon of the calcocambisols. Terra rossa receive acidic cations (H+ +Al3+) and their average value in the Amo horizon is 16,58 cmol(+)kg-1 soil (or 33,47% of Т), and 15,42 cmol(+)kg-1 soil (or 33,70% of T) in the (B)rz horizon.
Докторска дисертација одбранета во 2013 година на Факултетот за земјоделски науки и храна во Скопје, под менторство на проф. д–р Татјана Миткова.
Keywords: properties, mineral composition, chemical properties